Metarhizium anisopliae seed priming alleviates drought-induced oxidative stress and improves growth of barley (Hordeum vulgare L.) - Atofa Naz; Md. Motiar Rohman; Md. Ashraful Haque; Mahjabin Ferdaous Mim; Md. Zahid Hasan Chowdhury; Razia Sultana; Shah Mohammad Naimul Islam (Plant Stress)
Increasing crop resilience to drought stress through microorganisms is a sustainable approach. This study evaluated the efficacy of the endophytic fungus Metarhizium anisopliae MetA1 (MA) for improving drought tolerance of barley by analyzing various morphological, physiological, biochemical, and yield factors. Barley grains were treated with MA (1 × 108 spore/ml) and a pot experiment was conducted with three high-yielding barley genotypes: BARI Barley-10, BARI Barley-6, and BARI Barley-9 under three drought conditions: no drought (100 % field capacity, FC), moderate drought (50 % FC), and severe drought (25 % FC). Under drought conditions, MA priming significantly enhanced shoot and root biomass, leaf characteristics, photosynthetic pigment content, and activities of various antioxidant enzymes including superoxide dismutase, catalase, glutathione S-transferase, ascorbate peroxidase, peroxidase, glutathione peroxidase, glutathione reductase, dehydroascorbate reductase, monodehydroascorbate reductase, glyoxalase-I, and glyoxalase-II in all barley genotypes. Furthermore, there was an observed increase in the levels of non-enzymatic antioxidants such as ascorbate and glutathione. MA treatment also led to a significant reduction in stress markers like methylglyoxal, malondialdehyde, lipoxygenase, hydrogen peroxide, and calcium influx along with an increase in proline and potassium content in barley leaves in stressed conditions. Crop growth and yield related attributes in barley were improved, which is evidence of better physiological and biochemical changes under both stress and non-stressed conditions. As such, the study provides evidence suggesting that MA-mediated seed priming is an effective strategy for improving drought tolerance not only in barley but also possibly other crops.